Wellness Practices of Minority International Students: A Grounded Theory Study - Almaawali, Mahmood Salim (Journal of International Students, 2024)
As an important part of the fabric of college students, international minority students undergo specific and unique challenges to their health and wellness. Little is known about how and what constitutes wellness for minoritized international students and the impact of wellness on their university adjustment. Using a systematic grounded theory approach, this study interviewed 12 (8 men & 4 women) middle eastern international students (MEI). Following the constant comparison method and theoretical sensitivity, the study generated a wellness practices model for MEI students. Results showed that wellness had two levels: primary (physical, social, mental, and mindfulness) and secondary (religious, academic, and coping). Results have also shown that there are individual factors affecting how salient a wellness domain is in an individual’s life, such as optimism, hope, knowledge of self-care habits, and attitudes toward self-care. Implications for helping minoritized international are suggested considering wellness practices model.